REGIONAL PECULIARITIES OF USING PRODUCTION POTENTIAL OF THE MACRO-REGION AS A FACTOR OF RUSSIAN ECONOMY SUSTAINABILITY - Galina Yu. Gagarina; Lidiya S. Arkhipova (Вестник Российского экономического университета имени Г. В. Плеханова)
In current conditions of economic instability a serious role in providing sustainable development to Russian economy belongs to effective realization of economic potential of the country and its regions, including its component – production potential. In spite of a number of successive crises factors of stability keep being important for the country’s economy, which could raise sustainability to uncertainty on finance markets, external impact and ensure economic growth. They include, for example renovation and modernization of industrial enterprises, growth of investment in fixed assets, introduction of innovation, improvement of the quality of labour capital. In this connection the article shows the dynamics of key components of production potential and regional peculiarities of their use.